Afrocymbella barkeri sp. nov. (Bacillariophyta), a common phytoplankton component of Lake Challa, a deep crater lake in East Africa. Issue 2 (2nd April 2016) - Cocquyt, Christine; Ryken, Els
Abstract: A new freshwater diatom, Afrocymbella barkeri Cocquyt & Ryken sp. nov., is described from Lake Challa, a deep and unproductive crater lake near Mt Kilimanjaro in equatorial East Africa, based on light and electron microscopic observations. This tropical diatom is a representative of the rather small genus Afrocymbella with only 12 known species and with a distribution restricted to the African Rift. Taxa belonging to this genus are heteropolar and characterized by dorsiventral valves curved along the pervalvar axis and the presence of small pseudosepta and septa on the open girdle bands. Afrocymbella barkeri was common only towards the end of the dry and windy season corresponding to northern hemisphere summer, when deep water-column mixing caused upwelling of nutrient-rich water from the hypolimnion. This taxon was observed free living in the water column during mixing, but the presence of a small apical pore field at the foot pole, along with some cells with mucilage stalks, suggests that its primary habitat probably involves attachment to a substrate.